Studies on Haloalkaliphilic Bacteria Isolated from Lonar Meteorite Crater in India - Deepak U. Bhusare2, Sanjay S. Kulkarni2; Rajendra P. Mali3, Sunil D. Ahirrao1*, Sudarshan S. Pedge1, (Journal of Ecobiotechnology, 2011)
Haloalkaliphilic bacteria were isolated from water samples collected from alkaline Lonar meteorite crater, (MS) India having pH 10.5. Among them one of the bacterial strains was identified by 16S rRNA sequencing showed 97% alignment match with Bacillus fusiformis. The optimum growth of such organism was at 12.5 pH and 18% salt concentration. Chemical analysis of water showed higher amount of metal ions and salts concentrations present in lonar crater. The Bacillus fusiformis have potential to produce hydrolytic enzyme such as amylases. The amylase was partially purified by 80% ammonium sulphate and obtained 2 fold increase amylase activity. The optimum enzyme activity was at 10 pH and 30Ã‚Â°C temperature of. The enzyme was incubated in presence of different metal ions and showed its stability at 1mM concentration of MgSO4.